Media technologies : essays on communication, materiality, and society - Foot, Kirsten A.; Boczkowski, Pablo J.; Gillespie, Tarleton (Cambridge [etc.] MIT Press, 2014)
In recent years, scholarship around media technologies has finally shed the assumption that these technologies are separate from and powerfully determining of social life, looking at them instead as produced by and embedded in distinct social, cultural, and political practices
Keywords: Comunicación y tecnología; Medios digitales -- Aspectos psicológicos; Libros electrónicos